2023
DOI: 10.3389/fcell.2023.1219840
|View full text |Cite
|
Sign up to set email alerts
|

The role of ferroptosis in intervertebral disc degeneration

Abstract: Nucleus pulposus, annulus fibrosus, and cartilage endplate constitute an avascular intervertebral disc (IVD), which is crucial for spinal and intervertebral joint mobility. As one of the most widespread health issues worldwide, intervertebral disc degeneration (IVDD) is recognized as a key contributor to back and neck discomfort. A number of degenerative disorders have a strong correlation with ferroptosis, a recently identified novel regulated cell death (RCD) characterized by an iron-dependent mechanism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 219 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that exogenous ROS can induce apoptosis, necrosis, autophagy, and ferroptosis in NPCs [ 30 , 31 , 32 ]. To investigate the involvement of these pathways induced in NPCs by TBHP treatment, we utilized various inhibitors, including Z-VAD (a caspase-dependent apoptosis inhibitor), Necrostatin-1 (Nec-1; a necrosis inhibitor), 3-Methyladenine (3-MA; an autophagy inhibitor), Ferrostatin-1 (Fer-1; a ferroptosis inhibitor), and N-Acetyl-L-cysteine (NAC; an ROS inhibitor).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that exogenous ROS can induce apoptosis, necrosis, autophagy, and ferroptosis in NPCs [ 30 , 31 , 32 ]. To investigate the involvement of these pathways induced in NPCs by TBHP treatment, we utilized various inhibitors, including Z-VAD (a caspase-dependent apoptosis inhibitor), Necrostatin-1 (Nec-1; a necrosis inhibitor), 3-Methyladenine (3-MA; an autophagy inhibitor), Ferrostatin-1 (Fer-1; a ferroptosis inhibitor), and N-Acetyl-L-cysteine (NAC; an ROS inhibitor).…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is a unique form of regulated cell death characterized by iron-dependent lipid peroxidation. It has been reported that ferroptosis contributes to the pathogenesis of IVDD [ 47 ]. Puerarin has gained attention for its potential therapeutic effects in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent focus has been on ferroptosis, triggered by iron and ROS. Ferroptosis is linked to various degenerative disorders, and its role in IDD is emerging ( Fan et al, 2023b ). In the context of IDD, the ncRNA component, particularly circular RNAs present in extracellular vesicles derived from mesenchymal stem cells (MSC-EVs), assumes a critical role in mitigating ferroptosis.…”
Section: Exosomal Ferroptosis-related Ncrnas As Therapeuticsmentioning
confidence: 99%